Pengaruh Jumlah Penduduk dan Produk Domestik Regional Bruto Terhadap Penerimaan Pajak Daerah Pada 19 Kabupaten dan Kota Di Sumatera Barat Tahun 2015-2019 - Gerry Hamdani Putra; Evinda Rosliani (Fakultas Sastra Universitas Ekasakti, 2021)
Regional tax is an obligatory contribution to the region owed by an individual or entity that is compelling based on law without receiving direct compensation and is used for regional needs for the greatest prosperity of the people. This study aims to examine the Total Population and Gross Regional Domestic Product of Regional Tax Revenues in 19 districts and cities in west sumatera. This study uses local government revenue realization data in 19 districts and cities of west sumatera for the 2015-2019 period published by the Central Statistik Agency (BPS). Hypothesis testing uses panel data regression using the eviews 8.0 program. The results showed that population has a negative and significant effect on local tax revenue and gross regional domestic product has a positive and significant effect on local tax revenue.